Permanent Education as a strategy to transform the meaning of life of the health professional in the face of the pandemic: Prior note (Research, Society and Development, 2021)
The present study aims to inform about a research that propose to provide a space of action-reflection-action that promotes mental health of the health professional who works on the front line of COVID-19, to identify the working conditions that affect the mental health of health workers, describe the meaning of life and establish workshops to support, raise awareness and dialogue on mental health and self-care of health workers who work on the front line of COVID-19. For that, the chosen method will be an exploratory, descriptive research, with a qualitative approach, of the Convergent Assistance Research type. The research scenario will be the Intensive Care Center of a Reference Center COVID-19 in the region of Baia da Ilha Grande, in the State of Rio de Janeiro, with the participation of health workers in the sector. For data collection, two stages will be followed, one through the application of a semi-structured questionnaire, analyzed through Bardin's analysis, and the second through the realization of workshops based on the problematization methodology, through the use of the Maguerez Arch. We intend to discuss the results in the light of the theoretical framework of Donald Schon and Viktor E. Frankl and the political framework through the National Policy for Permanent Education in Health. With this study, we seek to contribute with an important step to establish the permanent education process to the health team in psychosocial support in caring for the victimized patient by COVID-19.